2017
DOI: 10.5539/ijel.v7n6p236
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Terminology in Reporting Islam: A Comparative Analysis

Abstract: The use of terminology in reporting Islam has been one of the major concerns of many scholars and religious experts in recent years. Specifically, the media's selection of words to describe Islam attracts attention of many righteous people. Words such as extremist, terrorist, militant, insurgent are mostly used to describe Muslims. This indicates the need to explore how the media particularly newspapers use terminology in reporting Islam, since people rely on the media for news and information. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 8 publications
(11 reference statements)
1
16
0
Order By: Relevance
“…A few studies focused specifically on the use of terms in Islam-related news (e.g. Allen, 2012;Hassan et al, 2017;Moore, Mason, & Lewis, 2008). These studies found that Islam-related terms are mostly used in a negative context, which might create negative perceptions of Islam and Muslims.…”
Section: News Coverage Of Islam In the Mediamentioning
confidence: 99%
See 4 more Smart Citations
“…A few studies focused specifically on the use of terms in Islam-related news (e.g. Allen, 2012;Hassan et al, 2017;Moore, Mason, & Lewis, 2008). These studies found that Islam-related terms are mostly used in a negative context, which might create negative perceptions of Islam and Muslims.…”
Section: News Coverage Of Islam In the Mediamentioning
confidence: 99%
“…The use of Islam-related terminologies in news coverage of Islam has become a contentious issue amongst scholars, researchers, and religious experts (Mohideen, & Mohideen, 2008;Reynolds, 2015;Hassan, Azmi, & Abubakar, 2017). The problem associated with the use of Islamrelated terms in the media arises when expressions are used without regard to their original connotations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations